论李世民音乐政治观对儒家礼乐思想的继承和转化 = A study on Li Shimin music-politics: inheritance and transformation of Confucian ritual and music thought - 许惠佳 Koh, Hwee Kay (2014)
唐初是一个政治稳定，经济繁荣与文化蓬勃发展的时代，不仅链接汉朝也下启盛唐的文化高峰。唐太宗李世民作为唐朝的第二位皇帝，正是这背后的推动者。李世民能在短时间内使唐初繁荣，不仅成为后世许多帝王学习的典范,也是众多学者研究的对象。然而，人们在看待李世民的政绩时，往往把目光放在其政治与经济理念上，很多时候忽略了他的文化主张和贡献。唐朝文化是由众多因素组成，呈现丰富且多元的样貌。在李世民的治理之下，文化的繁荣可见于音乐、宗教、书法等方面,而本文所要研究的范围就是唐初的音乐特点。贞观年间所实行的“开放政策”，提供了一个让不同民族文化交汇的平台，从而丰富了中原的文化。在这样的时代背景之下，李世民对于儒学的重视也使其音乐政治观承袭了《乐记》中的儒家礼乐思想。虽然如此，李世民并没有全盘接受并夸大礼乐的社会功能，而是接受了嵇康“声无哀乐”的音乐理论。有鉴于此，李世民独特的音乐见解是有研究的价值的。本文将考察李世民的音乐政治思想的特点，并以儒家音乐思想集大成的著作《乐记》为对照，揭示李世民音乐思想对于儒家礼乐思想的继承与转化。The Tang Dynasty was a period of Political stability, economic dominance and cultural advancement. It can be said that Tang Taizong Li Shimin played a pivotal role in shaping the early the Tang Dynasty, and his far-reaching influence made him the role model of many future kings. In keeping with this, there already exists extensive study and coverage on Li Shimin’s life and reign. However, the emphasis of most research works were on his politico-economic contributions and his cultural contributions remain largely understated, in particular the area of his Music-politics thought, which played a significant role during his governance. Under the influence of Li Shimin, the cultural aspect of the Tang Dynasty diversified and became established. During this period, the “Open Door Policy” provided a platform for the interaction of different cultures, which contributed to the growth in cultural diversity. In addition, Li Shimin also placed much emphasis on Confucianism and used it as one of his ruling measures. To a certain extent, he had inherited Yueji, Confucian ritual and Music thought - which extensively covers the social influence and educational function of music to society – while at the same time, his Music-politics thought bears much resemblance to those of Ji Kang. This article hopes to explore in detail Li Shimin’s Music-politics thought, and by using Yueji as a comparison, analyses how his inheritance and transformation of Confucian Ritual and Music thought played an important role in shaping the Tang Culture.